Chalcones from the Flowers of Coreopsis lanceolata and Their In Vitro Antioxidative Activity - Shang, Ya Fang; Oidovsambuu, Sarangerel; Jeon, Je-Seung; Nho, Chu Won; Um, Byung-Hun (Planta Medica, 2013)
Three new chalcones, 3,2′-dihydroxy-4,3′-dimethoxychalcone-4′-glucoside (1), 4′-O-(2′′′-O-caffeoyl)2′,3′,3,4-tetrahydroxychalcone (2), and 2′,4′,3-trihydroxy-3′,4-dimethoxychalcone (3), along with five known phenolics, were isolated from Coreopsis lanceolata flowers. The structures of the new compounds were elucidated by extensive spectroscopic methods including NMR and MS. The three new chalcones showed a good in vitro HepG2 cell protecting effect against tert-butylhydroperoxide-induced oxidative stress.
Keywords: antioxidative activity; Coreopsis lanceolata; Compositae; phenolics; chalcones